Turning EU into me and you: The politicization of EU representations in Macedonia - Aleksandar Takovski (Političke Perspektive, 2017)
EU is discursive field where multiple meanings are created, negotiated and contested. Research has shown that it has interpretive power often used as an instrument of political confrontation. Such is the case, this study argues, with the two largest Macedonian parties – the Social Democrats and VMRO -DPMNE – who in a pursuit of changing or maintaining power have produced an EU discourse fitting to their own political agendas. In a situation of a prolonged political crisis, and a significant EU involvement in it, the two parties have turned their EU discourse into an instrument of positive presentation of the self and a negative presentation of the other. The general goal of the study is to analyze the specific discursive strategies in the party programs and media statements of the two parties and their leaders.